2021
DOI: 10.3892/etm.2021.10646
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase‑1 alleviates advanced glycation end product‑induced oxidative stress, inflammatory response and biological behavioral disorders in rat dermal fibroblasts

Abstract: Advanced glycation end products (AGEs) are involved in delaying the wound healing of diabetic foot ulcers. The present study investigated the effects of heme oxygenase-1 (HO-1) on oxidative stress, inflammatory insult and biological behaviors in rat dermal fibroblasts in the presence of AGEs. Rat dermal fibroblasts were cultured in the presence of AGEs (100 µg/ml), glucose (1.0 g/l or 4.5 g/l), hemin (5 µM) and chromium mesoporphyrin (CrMP; 20 µM). A bilirubin kit, reverse transcription-quantitative PCR and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Besides, advanced glycation end products (AGEs) could induce oxidative stress and inflammatory responses in fibroblasts, which were closely related to fibroblast apoptosis 27 . Lao et al found that tissue inhibitor of metalloproteinases-1 (TIMP-1) levels were significantly reduced in AGEs-treated fibroblasts, and TIMP-1 could effectively reduce apoptosis 28 .…”
Section: Roles Of Apoptosis In Diabetic Wound Healingmentioning
confidence: 99%
“…Besides, advanced glycation end products (AGEs) could induce oxidative stress and inflammatory responses in fibroblasts, which were closely related to fibroblast apoptosis 27 . Lao et al found that tissue inhibitor of metalloproteinases-1 (TIMP-1) levels were significantly reduced in AGEs-treated fibroblasts, and TIMP-1 could effectively reduce apoptosis 28 .…”
Section: Roles Of Apoptosis In Diabetic Wound Healingmentioning
confidence: 99%
“…Irisin, a cleavage product of the type I membrane protein encoded by FNDC5, activates the Notch pathway and inhibits apoptosis in HUVECs and increases the expression of Bcl‐2 and VEGFA thereby accelerating wound healing 54 . Haeme oxygenase‐1 (HO‐1) is an antioxidant, anti‐inflammatory and cytoprotective enzyme that inhibits NHDF apoptosis and accelerates wound healing in diabetes 55 . Tissue inhibitor of metalloproteinase‐1 (TIMP‐1), a glycoprotein expressed in various tissues, promotes cell growth and inhibits apoptosis.…”
Section: Proteins Promote or Inhibit The Healing Of Dfusmentioning
confidence: 99%
“… 54 Haeme oxygenase‐1 (HO‐1) is an antioxidant, anti‐inflammatory and cytoprotective enzyme that inhibits NHDF apoptosis and accelerates wound healing in diabetes. 55 Tissue inhibitor of metalloproteinase‐1 (TIMP‐1), a glycoprotein expressed in various tissues, promotes cell growth and inhibits apoptosis. The levels of TIMP‐I are downregulated in diabetic foot skin tissue and AGE‐treated fibroblast culture supernatants, and increasing TIMP‐I expression can inhibit fibroblast apoptosis and accelerate wound healing in diabetic rats.…”
Section: Proteins Promote or Inhibit The Healing Of Dfusmentioning
confidence: 99%
“…This overproduction of cytokines leads to increased tissue damage and delayed diabetic wound healing. Also, prolonged hyperglycemia increases reactive oxygen species (ROS) production and oxidative injury. , Therefore, the primary reason for a longer healing time in diabetic wound patients is prolonged inflammation, and attenuation of inflammation and oxidative stress is essential to expedite the healing of diabetic wounds.…”
Section: Introductionmentioning
confidence: 99%